Analisis Kesejahteraan Penjual Pupuk Kandang di Desa Mencolok Kecamatan Mendahara Ulu - Muhammad Rizki; Agusriandi Agusriandi; Miftah Miftah (Tasyri' : Jurnal Muamalah dan Ekonomi Syariah, 2026)
This study aims to examine and analyze the welfare level of manure fertilizer sellers in Mencolok Village, Mendahara Ulu District, Tanjung Jabung Timur Regency, as well as to explore the role of manure fertilizer business in supporting the improvement of sellers’ family welfare and to identify various factors influencing these conditions. This research employs a qualitative method with a field research approach, focusing on an in-depth understanding of the socio-economic conditions of business actors within rural communities. Data were collected through in-depth interviews with informants, direct observation of business activities, and documentation as supporting data. The collected data were then analyzed using a descriptive qualitative technique to provide a comprehensive overview of the actual conditions in the field, particularly those related to the welfare of manure fertilizer sellers, the role of the business in supporting family economic life, and the internal and external factors affecting business sustainability. This study is also intended to offer broader insights into how micro-enterprises based on local resources can serve as an alternative for improving community living standards, especially in rural areas. Therefore, the findings of this research are expected to serve as an academic reference and as a consideration for village governments, related institutions, and business actors in formulating appropriate policies and strategies to support the development of manure fertilizer businesses and enhance community welfare sustainably.